Cable News Network : CNN apologizes to the Chinese people - Doi, Takashi; Munkel, Anielka; Morley, Phillip; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
On April 9, 2008, Jack Cafferty made comments concerning the United States relationship with China. These comments included calling the Chinese "goons and thugs" and labeling Chinese products "junk." Over the next month and a half, thousands of Chinese Americans organized outside of CNN studios across the U.S. demanding an apology from Cafferty and CNN. CNN responded with silence, clarifying statements, and thin apologies, all of which served to fuel negative opinion and ultimately elevate the story to international headlines.
Originally published in Doi, T., Munkel, A., Morley, P. & ORourke, J. S. (2009). Cable news network: CNN apologizes to the Chinese people. 09-06. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Cable News Network; Press -- Public relations; Issues management